2016
DOI: 10.1038/nature17998
|View full text |Cite
|
Sign up to set email alerts
|

NMDAR inhibition-independent antidepressant actions of ketamine metabolites

Abstract: Major depressive disorder afflicts ~16 percent of the world population at some point in their lives. Despite a number of available monoaminergic-based antidepressants, most patients require many weeks, if not months, to respond to these treatments, and many patients never attain sustained remission of their symptoms. The non-competitive glutamatergic N-methyl-D-aspartate receptor (NMDAR) antagonist, (R,S)-ketamine (ketamine), exerts rapid and sustained antidepressant effects following a single dose in depresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

66
1,108
11
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,314 publications
(1,196 citation statements)
references
References 40 publications
66
1,108
11
11
Order By: Relevance
“…However, ketamine still has limited clinical application, mainly because of its psychotomimetic side-effects and liability of abuse. A recent paper in Nature [5] showed that the ketamine metabolite enantiomer (2R,6R)-hydroxynorketamine (HNK) has rapid and sustained antidepressant effects without the side-effects associated with ketamine, such as abuse potential. The discovery of (R)-ketamine is a landmark in the field of depression.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, ketamine still has limited clinical application, mainly because of its psychotomimetic side-effects and liability of abuse. A recent paper in Nature [5] showed that the ketamine metabolite enantiomer (2R,6R)-hydroxynorketamine (HNK) has rapid and sustained antidepressant effects without the side-effects associated with ketamine, such as abuse potential. The discovery of (R)-ketamine is a landmark in the field of depression.…”
mentioning
confidence: 99%
“…Zanos et al [5] concentrated on ketamine metabolites and investigated the mechanism by which it exerts rapid and sustained antidepressant effects. The authors hypothesized that if ketamine has rapid-onset effects mainly by inhibiting NMDARs, then (S)-ketamine would be predicted to be more potent than (R)-ketamine, and alternative NMDAR inhibitors would also have similar effects.…”
mentioning
confidence: 99%
See 3 more Smart Citations